PENGARUH NILAI YANG DIRASAKAN DAN PENGALAMAN KONSUMSI TERHADAP LOYALITAS DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA CANAI MAMAK KL LAMTEH - Muhammad Ridha, Muhammad Adam (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
This study aims to determine the perceived impact and experience of Consumption on Loyalty with Customer Satisfaction as a mediation variable. Samples used in this study are 100 respondents who are consumers Canai Mamak KL Lamteh Banda Aceh. Purposive Sampling is used as a sampling technique. Partial Least Square Method (PLS) is used as a method of analysis to determine the effect of the variables involved. The results of this study show the perceived value and experience of consumption to loyalty. In addition, the results arise from Customer Satisfaction variables serve as a partial mediation on perceived Value of Values of Loyalty, and Customer Satisfaction serves as a full mediation on the variable of Consumption Experience on Loyalty. The higher Perceived Value and Consumption Experience, The Higher Customer Satisfaction, the stronger the Loyalty owned by the consumer.Perceived Value, Consumption Experience, Customer Satisfaction, Loyalty, Canai Mamak KL